Street Medical Consultation: health access of the Homeless People and intersectoral articulation. (30th September 2020) - Santos, D; Bombonati, G R; Marques, D; Vilela, M F G; Silva, E M
Abstract: Background: The Homeless People is marked by serious social vulnerability, related to the absence of human dignity. Requirements of personal and residential documents, reception and inadequate approaches are barriers to access these people. The creation of Street Medical Consultation (CnaR), based on the logic of harm reduction in association with the other services, is a strategy that seeks to expand access to the services of the Public Healthcare System (SUS) in Brazil. The research aimed to analyze the characteristics and vulnerabilities of this population, the performance of CnaR and its articulation with services from the health care and the social assistance care network. Methods: Study of a qualitative approach using 8 semi-structured interviews and the Thematic Content Analysis method. The study scenario was the CnaR multiprofissional team in a city in the interior of São Paulo. Results: Three categories were found: (1) Population in Street Situation - complexity of those who live on the street: prejudices, violence and barriers in society and health institutions constitute a process of invisibility. (2) CnaR's work in the perspective of harm reduction: it is organized to meet the clinical and alcohol and other drugs demands through fixed fields, mobile fields and team meeting. (3) Beyond CnaR - network relationships: bringing dynamics to relationships, being strengthened or weakened. Ignorance of the service and their performance also generates CnaR invisibility process. The strategies developed include coping, dialogue, building partnerships and the process of visibility and fighting for the rights of the Homeless Persons. Conclusions: CnaR finds itself as an insufficient service to meet all the demands of this vulnerable population in isolation, needing the network to expand access to health and other goods. It is necessary to combat prejudice against this population among health professionals and develop more efficient intersectoral articulation. Key messages: The Homeless People have serious vulnerability and need humanization, guaranteeing equity in assistance in all sectors of society, especially the health care and the social assistance. The Street Medical Consultation faces performance difficulties to guarantee access to the Homeless People within the intersectoral network, often being the sole responsible for this population.